(untitled) (Research, Society and Development, 2023)
This paper is written from the results of the research project entitled “Qualification processes in pandemic times: family perceptions about remote teaching”, developed at the Instituto Federal Farroupilha, campus São Borja. The objective is to analyze the perceptions of the family about monitoring the school life of their child(ren) in the situation of the adoption of remote and/or hybrid teaching, in the period of interruption of face-to-face teaching. It presents the following question as a research problem: what strategies is the family using in the task of monitoring the school life of their child(ren) in this moment of remote teaching? Supported by the contributions of qualitative research in its hermeneutic aspect, the investigation takes as a data collection instrument the written narratives that parents and/or guardians bring about monitoring the school life of their child(ren). In the analysis of the collected perceptions, three units of meaning are reached: routine organization; challenges in monitoring school life; and feeling the experience of monitoring school life, which are articulated in the understanding that the school assumes a sense of value, being important for the school life of the children. This sense of value appears in the cognitive and socialization aspects. It is evident, on the one hand, the identification of the school’s role as triggering the student’s learning and development and, on the other hand, that the strategies used by families to enhance the school performance of their children softened the impact generated by remote teaching, both in cognitive and socialization terms.